2008
DOI: 10.1586/14760584.7.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epitope information related toBacillus anthracisandClostridium botulinum

Abstract: We have reviewed the information about epitopes of immunological interest from Clostridium botulinum and Bacillus anthracis, by mining the Immune Epitope Database and Analysis Resource. For both pathogens, the vast majority of epitopes reported to date are derived from a single protein: the protective antigen of B. anthracis and the neurotoxin type A of C. botulinum. A detailed analysis of the data was performed to characterize the function, localization and conservancy of epitopes identified as neutralizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 100 publications
1
20
0
Order By: Relevance
“…Four different regions in the HC of the protein were selected for analysis (Table 1). These peptides are known to be important for antibody recognition since they were previously character-ized as highly sensitive epitopes (2,7,10,13,17,19). The antibodies generated against A1 could be significantly affected by the differences in these regions, even though the identity of the entire amino acid chains of A1 and A5 is close to 97%.…”
Section: Resultsmentioning
confidence: 99%
“…Four different regions in the HC of the protein were selected for analysis (Table 1). These peptides are known to be important for antibody recognition since they were previously character-ized as highly sensitive epitopes (2,7,10,13,17,19). The antibodies generated against A1 could be significantly affected by the differences in these regions, even though the identity of the entire amino acid chains of A1 and A5 is close to 97%.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive study was devoted in the past decade to develop second generation botulinum vaccines that are based on recombinant nontoxic fragments of the neurotoxin (47,52). The 50-kDa carboxy terminal of the neurotoxin heavy chain (Hc) was found to carry most of the neutralizing epitopes (58) and is the leading candidate for recombinant botulinum vac- (5). However, expression of recombinant Hc proteins in these systems met some major challenges, including the demand for laborious synthetic gene generation and difficulties in purifying the recombinant protein as a soluble secreted product (38,41).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the antigenic determinants of PA has shown a dearth of information on B-cell epitopes (50). In this regard, the peptide reactivity study provided additional information on the linear B-cell epitopes recognized by immune sera and previously generated MAbs.…”
Section: Discussionmentioning
confidence: 99%